Photovoice and Instagram as Strategies for Youth Engagement in Disaster Risk Reduction. (October 2022) - Pickering, Christina J.; Al-Baldawi, Zobaida; Amany, Raissa A.; McVean, Lauren; Adan, Munira; Baker, Lucy; Al-Baldawi, Zaynab; O'Sullivan, Tracey
Community involvement is essential for an all-of-society approach to disaster risk reduction. This requires innovative consultation methods, particularly with youth and during pandemic restrictions. This article outlines methods used for a Photovoice project where we brought together student co-researchers from multiple levels (high school, undergraduate, and graduate health sciences) to explore the topic of youth engagement in disaster risk reduction. Over a two-year period, our team used Photovoice as an arts-based participatory method to collaborate with members of our EnRiCH Youth Research Team. We adapted the protocol to continue our project during the COVID-19 pandemic and presented our work in a Photovoice exhibition using Instagram. This article was written from the perspectives of high school and university students on the project. Our hybrid Photovoice protocol facilitated participation through the pandemic, including a virtual presentation at an international conference and online consultation with the Canadian Red Cross.